2022
DOI: 10.3390/jpm12050807
|View full text |Cite
|
Sign up to set email alerts
|

A PDE Model of Breast Tumor Progression in MMTV-PyMT Mice

Abstract: The evolution of breast tumors greatly depends on the interaction network among different cell types, including immune cells and cancer cells in the tumor. This study takes advantage of newly collected rich spatio-temporal mouse data to develop a data-driven mathematical model of breast tumors that considers cells’ location and key interactions in the tumor. The results show that cancer cells have a minor presence in the area with the most overall immune cells, and the number of activated immune cells in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…This turns on intracellular and extracellular signaling pathways, helps hemangiomas grow in mice, and mimics the way human infantile hemangiomas grow [ 68 ]. Many studies have shown that PyMT is a key player in the growth of tumors and can cause cell death in vitro, which can lead to benign and malignant tumors in organs such as the skin, salivary gland, and mammary gland of mice [ 69 , 70 ]. Xu et al [ 71 ] made an IH animal model by microinjecting the PyMT transgenic DNA of polyomavirus into fertilized embryos, transferring them to mice that looked like they were pregnant, and observing the tumors in the newborn mice’s phenotypes and histological shapes (Fig.…”
Section: Transviral and Genetic Modelsmentioning
confidence: 99%
“…This turns on intracellular and extracellular signaling pathways, helps hemangiomas grow in mice, and mimics the way human infantile hemangiomas grow [ 68 ]. Many studies have shown that PyMT is a key player in the growth of tumors and can cause cell death in vitro, which can lead to benign and malignant tumors in organs such as the skin, salivary gland, and mammary gland of mice [ 69 , 70 ]. Xu et al [ 71 ] made an IH animal model by microinjecting the PyMT transgenic DNA of polyomavirus into fertilized embryos, transferring them to mice that looked like they were pregnant, and observing the tumors in the newborn mice’s phenotypes and histological shapes (Fig.…”
Section: Transviral and Genetic Modelsmentioning
confidence: 99%
“…propose a PDE model of breast cancer progression based on PyMT-MMTV mouse data. 35 Their results show that, in the regions with more immune cells interaction, cancer population is less dense, and a constant influx of immune cells controls the tumor size and cancer population. But, they do not further investigate the patterns formed in the tumor microenvironment and the pathways responsible for them.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches have been taken in the context of cancer modeling. Mohammad Mirzaei et al extends ODE models of breast cancer and colorectal cancer to reaction-diffusion-advection models coupled with mechanical growth to investigate the effect of immune cells heterogeneity on cancer progression [15,16]. Wang et al use morphoelasticity in a simple model to investigate the effect of mechanics on tumor spheroid growth [9].…”
Section: Introductionmentioning
confidence: 99%